2007
DOI: 10.1245/s10434-007-9391-y
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity in Giant Cell Tumors of Bone

Abstract: Giant cell tumors of bone (GCTB) are rare sarcomas with a high rate of unpredictable local relapse. Studies suggest that surgical methods affect recurrence, supporting the idea that local disease develops from re-growth of residual cancer cells. To identify early prognostic markers of individual risk of recurrence, we evaluated the effect of post-surgery fluids from a cohort of GCTB patients on growth of primary and established sarcoma cell lines, and mice xenograph. Post-surgery fluids increased cell growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…A recent study showed that ALT is not involved in GCTB (Forsyth et al, 2008). In line with previous results (Matsuo et al, 2007;Forsyth et al, 2008) we found expression of TERT, which encodes the catalytic subunit of telomerase, in all GCTBs, albeit at low and highly variable levels; the difference between the tumors with the highest and lowest expression levels was more than 50-fold. We could not, however, find any association between the expression level of TERT and telomere length or tas frequency.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A recent study showed that ALT is not involved in GCTB (Forsyth et al, 2008). In line with previous results (Matsuo et al, 2007;Forsyth et al, 2008) we found expression of TERT, which encodes the catalytic subunit of telomerase, in all GCTBs, albeit at low and highly variable levels; the difference between the tumors with the highest and lowest expression levels was more than 50-fold. We could not, however, find any association between the expression level of TERT and telomere length or tas frequency.…”
Section: Discussionsupporting
confidence: 92%
“…One possible explanation for the increased frequency of tas would be a general decrease in telomere length, but previous attempts using different approaches to investigate such a relationship have yielded conflicting results (Schwartz et al, 1993(Schwartz et al, , 1995Matsuo et al, 2007;Forsyth et al, 2008). The results of the present study provide further indirect and direct support for an important role of telomere shortening in tas formation in GCTB.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Support for this hypothesis was recently published (Sawyer et al, 2005;GebreMedhin et al, in press), but the causes of telomere dysfunction in GCTB, as well as the physical properties of tas, remain largely unknown. What has been revealed thus far is that there is a moderate reduction of telomere length in GCTB cells compared with normal tissues, despite telomerase activity, and that the majority of chromosome ends involved in tas are negative for telomeric sequences (Schwartz et al, 1993;Matsuo et al, 2007;Forsyth et al, 2008;GebreMedhin et al, in press).…”
Section: Introductionmentioning
confidence: 98%
“…3 In some reports, Campanacci grade III tumors demonstrated more aggressive behavior, 13,14 although statistical correlation has not been observed in other studies. [15][16][17] Campanacci grade III is defined as having indistinct borders on plain radiographs, 3 which generally, but not exclusively, predicts soft-tissue involvement histologically. Some authors have suggested that radiologic grade simply predicts the likelihood of adequate treatment, and it is the latter that influences clinical behavior.…”
mentioning
confidence: 99%